Socialization In Creating An Inclusive Society In For Children With Special Needs - Rona Wulandari; Utomo Utomo; Hayatun Thaibah; Mawarni Nurhidayah; Ayu Linda Frastya Frastya (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This initiative stemmed from the identification of an opportunity to raise public awareness and knowledge regarding children with special needs in a specific urban village in Banjarbaru City. The community service project aimed to foster an inclusive environment for children with special needs. Conducted in person with 54 participants, the program utilized a lecture-based format covering three key topics: types of disabilities, the roles of various stakeholders at the urban village level in building an inclusive community, and the introduction of an application for interventioning children with special needs. Pre- and post-test evaluations demonstrated an improvement in participant understanding. Assessments of participant satisfaction revealed a positive response to the event, which served to strengthen the community's inclusive perspective toward individuals with disabilities and encouraged cross-organizational collaboration in creating an inclusive environment at the urban village level.